Undergraduate Students’ Perception of Humata AI as A Writing Tool for Critical Journal Review (CJR) - Nst, Anggi Rahmanida; Dewi, Utami (Universitas Muhammadiyah Jember, 2025)
This study studies about students' perceptions of employing Humata AI for producing Critical Journal Reviews (CJR) and evaluates its advantages and limitations. Six students from a single University conducted semi-structured interviews employing a qualitative technique. Key themes in participant responses were identified using thematic analysis applied to the collected data. The majority of students indicated that Humata AI facilitated a more effective interpretation and evaluation of scientific papers. The primary advantages, particularly with structure and academic language, included the ease of uploading and obtaining journal summaries, increased confidence in writing, and the quality of academic writing. This study, however, also identified some flaws, including excessive dependence on technology, the reliability of analytical results that are not consistently appropriate, and concerns over the originality of student work. Consequently, our research indicates that while Humata AI provides significant benefits to students in the academic analysis process, its use must be complemented by traditional learning methods to ensure the development of critical thinking and independent academic writing skills. The results of this study have implications for educators and educational institutions in the ethical and effective integration into academic writing.